QUESTION ANSWERING FOR SUMEDANG LARANG KINGDOM USING THE MULTILAYER PERCEPTRON ALGORITHM - Arifa Nur Hasanah; Abdurahman Baizal; Ramanti Dharayani (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
In Indonesia, there were many kingdoms in the past, one of which was the Sumedang Larang Kingdom. Sumedang Larang is an Islamic kingdom under the control of the Pajajaran Kingdom. Through history, a nation will be able to recognize the origin of its own nation. Therefore, teaching about history is very important to be instilled from an early age. Through the rapid development of technology, teaching today is not only in the form of formal teaching, but also informal teaching. Nowadays, informal teaching can be done through various media, one of the media that is often used is gadgets. The utilization of gadgets as learning media allows a person to learn independently. One form of history learning by utilizing gadgets can be in the form of a Question Answering System (QAS). QAS allows users to ask questions using natural language and the system will answer the questions. Therefore, our research aims to help introduce the history of the Sumedang Larang kingdom to the public. We build a QAS by utilizing the n-gram model, Multilayer Perceptron (MLP) algorithm, and ontology. N-gram is used to cut words/sentences and convert them into a matrix, while MLP is used to classify texts, and ontology is used as knowledge representation. In this study, the system was able to answer 35 questions out of 61 questions, so it had an accuracy of 57.37%.